Airborne measurements of western U.S. wildfire emissions: Comparison with prescribed burning and air quality implications. Issue 11 (14th June 2017) - Liu, Xiaoxi; Huey, L. Gregory; Yokelson, Robert J.; Selimovic, Vanessa; Simpson, Isobel J.; Müller, Markus; Jimenez, Jose L.; Campuzano‐Jost, Pedro; Beyersdorf, Andreas J.; Blake, Donald R.; Butterfield, Zachary; Choi, Yonghoon; et al.
Abstract: Wildfires emit significant amounts of pollutants that degrade air quality. Plumes from three wildfires in the western U.S. were measured from aircraft during the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) and the Biomass Burning Observation Project (BBOP), both in summer 2013. This study reports an extensive set of emission factors (EFs) for over 80 gases and 5 components of submicron particulate matter (PM1 ) from these temperate wildfires. These include rarely, or never before, measured oxygenated volatile organic compounds and multifunctional organic nitrates. The observed EFs are compared with previous measurements of temperate wildfires, boreal forest fires, and temperate prescribed fires. The wildfires emitted high amounts of PM1 (with organic aerosol (OA) dominating the mass) with an average EF that is more than 2 times the EFs for prescribed fires. The measured EFs were used to estimate the annual wildfire emissions of carbon monoxide, nitrogen oxides, total nonmethane organic compounds, and PM1 from 11 western U.S. states. The estimated gas emissions are generally comparable with the 2011 National Emissions Inventory (NEI). However, our PM1 emission estimate (1530 ± 570 Gg yr −1 ) is over 3 times that of the NEI PM2.5 estimate and is also higher than the PM2.5 emitted from all other sources in these states in the NEI. This study indicates that the source of OA from biomass burning in the western states is significantly underestimated. In addition, our results indicate that prescribed burning may be an effective method to reduce fine particle emissions. Key Points: Emission factors (EFs) were measured for three western wildfires for major gases and particles and rarely measured OVOCs and organic nitrates Aircraft‐measured EF(PM1 ) from wildfires is more than 2 times that of prescribed fires Emission estimates for western U.S. wildfires indicate a significant BB contribution to aerosol mass Plain Language Summary: Wildfires emit large amounts of pollutants. This work quantifies the emissions of a range of both gaseous and particulate species from U.S. wildfires using measurements performed on research aircraft. The results indicate that wildfires are a large source of particulate pollution in the western states and that the source is currently underestimated by more than a factor of three in emissions inventories. Comparison of these results to those obtained from prescribed burning indicates that wildfires are a larger source of pollution.